P052 Comparing T cell responses to food antigens in Inflammatory Bowel Disease patients and healthy donors. (21st January 2022) - Schiffer, A; Tran, F; Sievers, L K; Kümpers, J; Hinrichsen, H; Seegers, B; Bergfeld, A; Lessing, M; Schreiber, S; Bacher, P
Abstract: Background: The role of nutrition in Inflammatory Bowel Disease (IBD) remains unclear. Studies about the effects of nutritional components on intestinal inflammation and the gut microbiome, as well as the concept of exclusive enteral nutrition in paediatric Crohn's Disease (CD) are suggestive of an impact of nutrition on the pathophysiology. However, there is currently a lack of knowledge on how food components may affect IBD. Here, we investigated the T helper (Th) cell response against nutritional antigens in healthy controls and IBD patients. Methods: We used a highly sensitive and specific method developed in our lab, the antigen reactive T cell enrichment (ARTE), to detect wheat and milk-reactive CD4+ T cells directly ex vivo in blood of healthy controls (n=18), CD (n=17) and Ulcerative Colitis (UC, n=15) patients. Peripheral blood mononuclear cells (PBMC) were incubated with whole antigen lysates and activated T helper cells were identified based on the up-regulation of the activation marker CD154. Magnetic enrichment of CD154 positive cells enabled to collect sufficient numbers of food-reactive T cells for their detailed characterization by multiparameter flow cytometry. Results: We detected low frequencies of milk and wheat-reactive T cells in healthy individuals. Milk-reactive T cells were less frequent and expressed several markers of T cell exhaustion. In CD, but not UC patients, we identified higher frequencies of food-reactive T cells. These tended to be particularly increased in patients with disease manifestation in the upper gastrointestinal tract. In addition, we observed increased production of inflammatory cytokines of wheat-reactive T cells in CD, compared to healthy controls and UC patients. No ground-breaking differences were identified regarding the expression of exhaustion markers between IBD patients and controls. Conclusion: Frequencies of food-reactive Th cells are increased in CD and show a proinflammatory cytokine pattern. The Th1-response of wheat-reactive T cells, characterized by high IFN-γ-secretion, might contribute to the perpetuation of chronic intestinal inflammation.